Targeting neuroinflammation: a critical opportunity in the evolving landscape of neuropharmacology - Sinha, Soham (International Journal of Basic & Clinical Pharmacology, 2026)
Neurodegenerative disorders such as Alzheimer’s disease (AD), Parkinson’s disease (PD), amyotrophic lateral sclerosis (ALS), and frontotemporal dementia continue to impose an escalating global health burden, yet therapeutic progress has remained disappointingly slow. For decades, neuropharmacology has been dominated by symptomatic approaches-cholinergic modulation, dopaminergic replacement, or glutamatergic stabilization-offering only transient relief without modifying disease trajectory. However, emerging evidence indicates that neuroinflammation is a central, unifying pathological mechanism across neurodegenerative diseases. This paradigm shift has catalyzed a new wave of drug development targeting microglial activation, inflammasomes, complement pathways, and neuroimmune signalling. There is now a compelling need to accelerate translational efforts in this domain, particularly in low-and middle-income countries where the incidence of neurodegenerative disorders is rapidly rising.